A qualitative exploration to inform an oral health training for disability care workers in Burkina Faso - Põld, Ave; Kientega, Dan Filwendé; Garé, Jocelyne Valérie; Lorenz, Michael (Nursing open, 2024)
Aim To explore enablers and barriers to the creation of an oral health training for care workers at specialized centres for children with disabilities in Ouagadougou. Design This was a formative study informed by the Theoretical Domains Framework using qualitative methods. Methods Qualitative observations and 14 semi-structured interviews were conducted with care workers from six specialized centres for disability. Results Carer workers emphasized that a successful oral health training must account for available resources and competencies in each specific centre. Part of the training must be dedicated to oral hygiene targeted for people with disabilities and provide knowledge about risk factor management. Care workers must be empowered through the training with practical skills and tools to manage regular toothbrushing and identify oral health needs of their dependents. Conclusion This study gathered valuable and unique perspectives about the roles of care workers of children with disabilities in Ouagadougou and underscores the need for improving access to oral health and care services for children with disabilities in low-resourced settings. Implications for Patient Care Teams planning oral health promotion activities in low resourced settings for vulnerable population groups can benefit from the methodology and results of this research for ensuring their interventions are appropriate and relevant. Impact This is a unique field study conducted in a scarcely researched area of caregiving practices for children with disabilities in a low-income country, Burkina Faso. Results from the disability centre observations and interviews with local caregivers are of great value to any team planning health projects in similar low-resourced settings. Psychiatric and mental health nursing practices are highly context-dependent, thus using proposed qualitative methods can help to ensure that planned interventions are appropriate and relevant. Patient or Public Contribution There was no patient contribution in this study.
Online veröffentlicht: 21. August 2024
Gesehen am 20.03.2025